Natural products targeting glycolysis in cancer - Zhao, Yuanyuan; Chard Dunmall, Louisa S; Cheng, Zhenguo; Wang, Yaohe; Si, Lingling (Frontiers in Pharmacology, 2022)
Many energy metabolism pathways exist in cancer, including glycolysis, amino acid metabolism, fatty acid oxidation, and mitochondrial respiration. Tumor cells mainly generate energy through glycolysis to maintain growth and biosynthesis of tumor cells under aerobic conditions. Natural products regulate many steps in glycolysis and targeting glycolysis using natural products is a promising approach to cancer treatment. In this review, we exemplify the relationship between glycolysis and tumors, demonstrate the natural products that have been discovered to target glycolysis for cancer treatment and clarify the mechanisms involved in their actions. Natural products, such as resveratrol mostly found in red grape skin, licochalcone A derived from root of Glycyrrhiza inflate, and brusatol found in Brucea javanica and Brucea mollis, largely derived from plant or animal material, can affect glycolysis pathways in cancer by targeting glycolytic enzymes and related proteins, oncogenes, and numerous glycolytic signal proteins. Knowledge of how natural products regulate aerobic glycolysis will help illuminate the mechanisms by which these products can be used as therapeutics to inhibit cancer cell growth and regulate cellular metabolism.